Analisis Penerapan Sistem Sirekap dalam Pengelolaan Arsip Akta Kematian di Dinas Kependududkan dan Pencatatan Sipil Kota Tanjungpinang - Dea Putri Rahmadhani; Dwi Aprilia; Nazaki Nazaki; Nur Aslamaturrahmah Dwi Putri (CV. ITTC INDONESIA, 2026)
The development of information technology encourages government agencies to implement digital systems in the management of population administration, including the management of death certificate archives. One of the innovations used by the Tanjungpinang City Population and Civil Registration Office is the Population Archives Record Information System (SIREKAP). This study aims to analyze the application of SIREKAP in the management of death certificate archives at the Tanjungpinang City Population and Civil Registration Office. The research uses a qualitative descriptive method with data collection techniques through observation, interviews, and document. the research informations consist of employees involved in the management of death certificate archives and the operation of SIREKAP. The results of the study show that the implementation of SIREKAP helps the process of recording, storing, and searching death certificate archives to be faster, more organized, and more accessible compared to manual filing systems. In addition, this system supports document security and improves the efficiency of population administration services. However, in its implementation, several obstacles are still found, such as internet network disruptions, the need to improve the ability of human resources in operating the system, and the need for regular system maintenance. Therefore, improving the quality of human resources and strengthening information technology infrastructure is needed to support the optimization of digital archive management within the Tanjungpinang City Population and Civil Registration Office.